Produção de biodiesel em um reator de micro-ondas utilizando catálise homogênea e heterogênea, e o desenvolvimento de modelos quimiométricos para quantificação - Sabrina Nogueira Rabelo (2015)
In this study, it the feasibility of production of biodiesel in a microwave-assisted reactor was verified. The transesterification reaction was carried out using soybean oil and methanol as esterifying agent. Homogeneous catalysis using sodium methoxide as a catalyst and heterogeneous catalysis were tested in order to verify the compatibility with microwave irradiation. The heterogeneous catalyst was prepared with chicken egg shells as precursor material. The analytical techniques used for quantification of the methyl esters present in the biodiesel were gas chromatography and Fourier transform infrared spectroscopy (FTIR). A model designed using the spectra generated by FTIR coupled with a partial least squares regression (chemometric model), proved to be a fast and reliable method to quantify biodiesel. The study demonstrated that irradiation by microwaves can reduce the reaction time for biodiesel production from hours to a few minutes when compared with the conventional mechanical mixing method. The use of microwaves employing heterogeneous catalysis coupled with FTIR analysis are very promising methods for the biodiesel industry, since they can significantly reduce costs and time of production and analysis.